Respostas metabólicas e de crescimento de matrinxãs (Brycon cephalus, Günther, 1869) submetidos ao exercício sustentado - Hackbarth, Araceli (2004)
The fish farm is becoming a promising commercial activity, however, in Brazil only 1% of the fish culture potential is explored, meanly due to the lack of studies on our Neotropical fish. The matrinxã, Brycon cephalus, is very appreciated species for many qualities as fast growth, easy adaptation to commercial food and exquisite tasty fillet. Like reofilic fishes, the rapids are their natural environment, making these species an ideal subject for studies that correlate exercise and growth. There are many kinds of activities in which fish can swim against water current at different speeds and length of time. The strenuous exercises, besides few experienced in vivo, present serious metabolic disturbances. On the other hand, the sustained swimming can improve the feed conversion rate and the growth. Such modifications are also expected for less active fish, since adequate speeds are reached for them. In this kind of exercise aerobic metabolism is preferential and it can be maintained for long periods without present fatigue. For all such, the purpose of this work was to appraise the effects of sustained swimming on the performance of matrinxã, submitted to sustained swimming for 37 and 72 days at 42 cm.s-1. Eighty matrinxãs were randomly divided in four groups of twenty fish (45 ± 17g; 14 ± 2cm). Two of these groups were exercised in circulating-water tanks (E37 and E72), swimming counter current for 37 and 72 days, respectively, at 42cm.s-1. The other two groups (C37 and C72) remained in static-water tanks for the same trial periods. At the end of each trial period, 13 fish from each group were weighed, the size was gauged, and blood samples were collected for growth, hematological, ions and metabolite determinations. After these procedures, fish were killed and liver, white and red muscles were excised, in order to determine the metabolite responses, the metabolic enzyme activities and the RNA/protein rate. The matrinxãs presented different responses for different periods of exercise. However, the exercise improved the growth rates for both exercised groups, with decrease of protein consume for energetic demands. The hematological responses of both exercised groups point to a better oxygen and nutrient transport, in spite of the major energy cost. Spite of E72 group had consumed proteins, matrinxãs incorporated more amino acids and protein in their white muscle, which improved the matrinxã growth rate. The reduced levels of sugars, glycogen and lipids in E72 white muscle indicate that matrinxã exercised for 72 days, utilizes preferentially the glycolytic and lipid pathways. The better-feed conversion rates plus the major growth of exercised matrinxãs, meanly in E72, make us sure that moderate exercise is recommended as a good practice for matrinxã farming.